2015
DOI: 10.1017/s0033291715002032
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in adult reporting of adverse childhood experiences

Abstract: Concurrent mental health factors may influence the reporting of traumatic childhood experiences. Studies that use retrospective reporting to estimate associations between childhood adversity and adult outcomes associated with mental health may be biased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
160
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 40 publications
2
160
1
1
Order By: Relevance
“…Inconsistent reporting was most commonly attributable to events being reported at baseline but not at follow-up. The presence of some temporal disagreement in event reporting is in line with research indicating that retrospective recall of trauma can fluctuate and is influenced by people’s current mental state (Colman et al, 2016), Further, the temporal stability of the TALE is in line with gold standard trauma assessment measures such as the Trauma History Questionnaire (Mueser et al, 2001), particularly in relation to lower reliability for ‘other events’ items (Hooper et al, 2011). …”
Section: Discussionsupporting
confidence: 82%
“…Inconsistent reporting was most commonly attributable to events being reported at baseline but not at follow-up. The presence of some temporal disagreement in event reporting is in line with research indicating that retrospective recall of trauma can fluctuate and is influenced by people’s current mental state (Colman et al, 2016), Further, the temporal stability of the TALE is in line with gold standard trauma assessment measures such as the Trauma History Questionnaire (Mueser et al, 2001), particularly in relation to lower reliability for ‘other events’ items (Hooper et al, 2011). …”
Section: Discussionsupporting
confidence: 82%
“…Another possibility is that current anxiety and depression may increase the tendency to recollect and report life events in a more negative and traumatic way [59,60], thus strengthening the negative association with mental health problems. However, those experiencing good times may also be inclined to report fewer adverse childhood events, thus weakening the negative association with mental health [61]. …”
Section: Discussionmentioning
confidence: 99%
“…Third, reports by both groups could have been impacted by recall bias, which may have contributed to either over- or underreporting experiences of childhood adversity. Recent studies have found that both types of biased recall are related to psychological well-being at the time of assessment, with depression, chronic stress, and increased distress related to greater inconsistencies in reporting (Colman et al, 2016). These factors may also have impacted patients' ability to report on past events.…”
Section: Discussionmentioning
confidence: 99%